2011
DOI: 10.1093/arclin/acr015
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the MMPI-2 Response Bias Scale and Henry-Heilbronner Index in a U.S. Veteran Population

Abstract: The Response Bias Scale (RBS) and the Henry-Heilbronner Index (HHI) are two recently developed Minnesota Multiphasic Personality Inventory-2 (MMPI-2) validity scales empirically derived for the purpose of detecting feigned symptom report. Utilizing a veteran sample, the present study examined the utility of these and other MMPI-2 validity scales in predicting Word Memory Test (WMT) failure and presence of recent, current, or upcoming compensation evaluation. Although a significant predictor of WMT performance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…As the current study evaluated only clinically referred veterans with a history of mTBI, and as the sample was thus fairly homogenous in terms of education (typically high school or greater), ethnicity (majority Caucasian), age, and injury characteristics, the generalizability of our findings to other populations-particularly older individuals and/or those with other neurological conditions such as dementia, stroke, or more severe TBI-is uncertain. Also, a relatively large proportion of our sample ( 66%) performed below recommended cut scores on at least one PVT, although this degree of PVT failure is comparable with rates seen in other studies evaluating similar populations (e.g., Armistead-Jehle, 2010;Whitney, Davis, Shepard, & Herman, 2008;Young, Kearns, & Roper, 2011;Young, Baughman, & Roper, 2012). Nonetheless, base rates play a considerable role in clinical decision-making, and can of course significantly affect the positive and negative predictive values of PVTs (e.g., Victor et al, 2009), resulting in potentially differing preferences for the number of failed PVTs to be used as a marker of data invalidity.…”
Section: Discussionsupporting
confidence: 86%
“…As the current study evaluated only clinically referred veterans with a history of mTBI, and as the sample was thus fairly homogenous in terms of education (typically high school or greater), ethnicity (majority Caucasian), age, and injury characteristics, the generalizability of our findings to other populations-particularly older individuals and/or those with other neurological conditions such as dementia, stroke, or more severe TBI-is uncertain. Also, a relatively large proportion of our sample ( 66%) performed below recommended cut scores on at least one PVT, although this degree of PVT failure is comparable with rates seen in other studies evaluating similar populations (e.g., Armistead-Jehle, 2010;Whitney, Davis, Shepard, & Herman, 2008;Young, Kearns, & Roper, 2011;Young, Baughman, & Roper, 2012). Nonetheless, base rates play a considerable role in clinical decision-making, and can of course significantly affect the positive and negative predictive values of PVTs (e.g., Victor et al, 2009), resulting in potentially differing preferences for the number of failed PVTs to be used as a marker of data invalidity.…”
Section: Discussionsupporting
confidence: 86%
“…The test has been validated in a wide variety of veteran samples (veterans with comorbid posttraumatic stress disorder (PTSD) and concussion, Nelson et al, 2011; sexually traumatized female veterans, Arbisi, Erbes, Polusny, & Nelson, 2010; soldiers with mild traumatic brain injury, Arbisi, Polusny, Erbes, Thuras, & Reddy, 2011); in these studies, some small, but mostly medium to large effect sizes were reported. Its validity scales have been previously found to detect cognitive/somatic (Jones & Ingram, 2011; Jones, Ingram, & Ben-Porath, 2012; Young, Kearns, & Roper, 2011) and/or psychiatric symptom overreporting (Tolin, Steenkamp, Marx, & Litz, 2010) in veterans, generally demonstrating moderate to large effect sizes. However, despite the potential theoretical and clinical relevance of the MMPI-2-RF domains for assessing varying levels of suicide risk, no studies to date have examined the utility of the MMPI-2-RF for this purpose in veteran populations.…”
Section: The Mmpi-2-rfmentioning
confidence: 99%
“…Whitney, Davis, Shepard, and Herman (2008) found a high rate of SVT failure as 48% of veterans routinely referred for outpatient evaluations failed the Test of Memory Malingering (TOMM; Tombaugh, 1996). Young, Kearns, and Roper (2011) found a similar rate of SVT failure as 49% of veterans performed below recommended cutoffs on the Word Memory Test (WMT; Green, 2003) irrespective of evaluation context (i.e., compensation seeking versus non-compensation seeking). In a sample of 45 veterans referred following failure of a second-level TBI screening, Armistead-Jehle (2010) found that 58% failed the Medical Symptom Validity Test (MSVT; Green, 2004).…”
Section: Introductionmentioning
confidence: 99%